Evaluación de remoción de plomo por acción de perlas de alginato con Chlorella sp. inmovilizada - Triviño Tonato, Nidia Geovanna (2018)
Lead is a heavy metal used in mining and fuel, it is highly toxic to bioaccumulate at different trophic levels, causing serious environmental problems. The microalga Chlorella has presented great potential in the remediation of heavy metals. This investigation proposed to evaluate the removal of lead by the action of alginate beads with this immobilized microalga and as a control alginate beads without microalga. Lead removal capacity was analyzed by the kinetic study of adsorption on calcium alginate beads, evaluating the effect of pH 4 and 5 as well as the incorporation of the microalga at concentrations 0.3x107, 1.6x107, 3x107 cells/ mL of alginate. To measure the concentration of lead in the aqueous solutions, atomic absorption spectrophotometry was used. It was evidenced that the maximum lead removal occurs in times close to 143 minutes; while variables as pH, cell concentration and different concentrations of the metal did not have significant effect on the removal of this metal. There is no directly proportional relationship between the concentration of the immobilized microalgae and the ability to remove Pb. Finally, we compared the discrepancy in the ability to remove alginate beads with Chlorella, alginate beads without Chlorella and Chlorella without immobilizing to different concentrations of metal (0-20 mg / L) in the solution, showing that the treatment with alginate beads without Chlorella remove more of the contaminant, since the alginate individually also shows removal action.